Mass-wasting features and processes in Vesta’s south polar basin Rheasilvia - Otto, Katharina A.; Jaumann, R.; Krohn, Katrin; Matz, Klaus-Dieter; Preusker, Frank; Roatsch, Thomas; Schenk, Paul; Scholten, Frank; Stephan, Katrin; Raymond, C.A.; Russell, C.T. (Journal of Geophysical Research: Planets, 2013)
The Rheasilvia crater is Vesta's largest impact basin. It is a 500 km diameter complex crater centered near the south pole and overlying the 400 km diameter impact basin Veneneia. Using Framing Camera (FC) data from the Dawn spacecraft's Low Altitude Mapping Orbit (20 m/pixel) and a digital terrain model derived from High Altitude Mapping Orbit stereo data, we identified various mass-wasting features within the south polar region. These features include intra-crater mass movements, flow-like and creep-like structures, slumping areas, landslides, and curved radial and concentric ridges. Intra-crater mass-wasting features are represented by lobate slides, talus material, dark patches on the crater wall, spurs along the crater rim and boulders. Slumping areas develop in compact material, whereas landslides form in relatively loose material. Both may be triggered by seismic shaking induced by impacts. Intra-crater mass wasting and slid and slumped materials are homogeneously distributed throughout the basin. Slumping and sliding processes have contributed most efficiently to basin degradation. Flow-like and creep-like features originate from granular material and cluster between 0°E and 90°E, an area exposing shocked and fractured material from the Rheasilvia impact event. The radial curved ridges are likely to be remnants of the early Rheasilvia collapse process, when radially moving masses were deflected by the Coriolis Effect. The concentric ridges are artifacts from the crater rim collapse. Curved ridges at the intersection of Rheasilvia and Veneneia, and on Rheasilvia's central peak, may also have been influenced by the Rheasilvia basin relaxation process, and an oblique impact, respectively.